2009
DOI: 10.2478/s11532-009-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable carbonated hydroxyapatite Ca10−xNax(PO4)6−x(CO3)x(OH)2 powders for bioactive materials preparation

Abstract: The purpose of this work was to find and investigate a correlation between the carbonate ion content in crystalline lattice and defect structure, and solubility of the materials; finally, to prepare the materials under study for in vitro tests. Various techniques, such as XRD, FTIR, TEM, FESEM/EDX, TG/DTA, AES (ICP), wet chemical analysis, Ca-ionometry, microvolumetric analysis of evolved CO2, BET adsorption, were applied to determine the efficiency of carbonate substitution, and to quantify the elemental comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Then, the precipitates were filtered, thoroughly washed with 1 l of distilled water and allowed to dry at room temperature (RT) overnight. Other details of the synthesis and post-synthesis treatments are given in [17,18]. 55…”
Section: Synthesis Of Hap Powdersmentioning
confidence: 99%
“…Then, the precipitates were filtered, thoroughly washed with 1 l of distilled water and allowed to dry at room temperature (RT) overnight. Other details of the synthesis and post-synthesis treatments are given in [17,18]. 55…”
Section: Synthesis Of Hap Powdersmentioning
confidence: 99%
“…In particular, it presents an average content of about 6% in weight of carbonate ions, which may substitute both hydroxyl groups in the c ‐axis channel of apatite (“type A” substitution) and/or phosphate groups (“type B” substitution) . The two substitutions usually coexist in a solid solution (giving rise to mixed type A‐B substitutions) in carbonated hydroxylapatite (COHAp), and the order of occurrence of type A and type B substitutions were extensively studied . The effects of type A, type B, and type A‐B substitutions on the unit cell variations and on the spatial orientation of the carbonate ion within the OHAp lattice were extensively studied at both the experimental and theoretical levels, aiming at a better comprehension of the mineralization, demineralization, and remineralization properties of carbonated hydroxylapatite.…”
Section: Introductionmentioning
confidence: 99%
“…5 Studies have also showed that the dissolution rates of synthetic cHAP powders were higher in comparison to pure HAP and the bioactivity of samples increased with increasing carbonate content. 4 The higher osteoconductive properties and earlier bioresorption of the cHAP implants, as compared to HAP samples, were also reported. 6 Conventionally, synthetic apatites are produced by a wet synthesis approach when precipitates of calcium phosphates in the amorphous or crystalline phase are directly formed under mixing calcium and phosphate ions.…”
Section: Introductionmentioning
confidence: 84%